Proceedings of the 2018 Conference of the North American Chapter Of the Association for Computational Linguistics: Hu 2018
DOI: 10.18653/v1/n18-1118
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Discourse Phenomena in Neural Machine Translation

Abstract: For machine translation to tackle discourse phenomena, models must have access to extrasentential linguistic context. There has been recent interest in modelling context in neural machine translation (NMT), but models have been principally evaluated with standard automatic metrics, poorly adapted to evaluating discourse phenomena. In this article, we present hand-crafted, discourse test sets, designed to test the models' ability to exploit previous source and target sentences. We investigate the performance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
261
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(275 citation statements)
references
References 20 publications
9
261
1
4
Order By: Relevance
“…Recent studies revealed that inter-sentential context can implicitly help to tackle anaphora resolution in NMT architecture (Jean et al, 2017b;Bawden et al, 2018;Voita et al, 2018). Some may argue that document-level architectures are strong enough to alleviate ZP problems for NMT.…”
Section: Effect Of Discourse-level Contextmentioning
confidence: 99%
“…Recent studies revealed that inter-sentential context can implicitly help to tackle anaphora resolution in NMT architecture (Jean et al, 2017b;Bawden et al, 2018;Voita et al, 2018). Some may argue that document-level architectures are strong enough to alleviate ZP problems for NMT.…”
Section: Effect Of Discourse-level Contextmentioning
confidence: 99%
“…By ignoring discourse connections between sentences and other valuable contextual information, this simplification potentially degrades the coherence and cohesion of a translated document (Hardmeier, 2012;Meyer and Webber, 2013;Sim Smith, 2017). Recent studies (Tiedemann and Scherrer, 2017;Wang et al, 2017; have demonstrated that adding contextual information to the NMT model improves the general translation performance, and more importantly, improves the coherence and cohesion of the translated text (Bawden et al, 2018;Lapshinova-Koltunski and Hardmeier, 2017). Most of these methods use an additional encoder Wang et al, 2017) to extract contextual information from previous source-side sentences.…”
Section: Introductionmentioning
confidence: 99%
“…Developing document-level models for machine translation has been an important research direction, both for conventional SMT (Gong et al, 2011;Hardmeier et al, 2012;Xiong et al, 2013a,b;Garcia et al, 2014) and NMT (Jean et al, 2017;Kuang et al, 2017;Tiedemann and Scherrer, 2017;Wang et al, 2017;Maruf and Haffari, 2018;Bawden et al, 2018;Tu et al, 2018;Voita et al, 2018).…”
Section: Related Workmentioning
confidence: 99%
“…While document-level NMT has attracted increasing attention from the community in the past two years (Jean et al, 2017;Kuang et al, 2017;Tiedemann and Scherrer, 2017;Wang et al, 2017;Maruf and Haffari, 2018;Bawden et al, 2018;Tu et al, 2018;Voita et al, 2018), to the best of our knowledge, only one existing work has endeavored to model document-level context for the Transformer model (Voita et al, 2018). Previous approaches to document-level NMT have concentrated on the RNNsearch model (Bahdanau et al, 2015).…”
Section: Introductionmentioning
confidence: 99%